The usefulness and usability of moodle LMS as employed by Zarqa University in Jordan (Journal of Information Systems and Technology Management, 2019)
This research investigates the usefulness and usability of Moodle LMS, as employed by a case study university (Zarqa University), based on students’ experience with Moodle LMS on desktop/laptop and mobile/tablet interfaces. A total of 320 students participated in this research in two stages. The results of this research showed that the students at Zarqa University used frequently only two features on Moodle on both its interfaces. The results of this research also showed that a large number of the students required the provision of 15 features on the local instance of Moodle which are not currently provided. Furthermore, the results showed that a large number of the students identified nine usability problems on the interfaces of Moodle, and a large number suggested nine improvements to the design of Moodle to make it more usable. Finally, this research suggests recommendations to improve the usefulness and usability of Moodle LMS as used by the case study university.